2021
DOI: 10.1212/cpj.0000000000001025
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Safety Analysis of 2,999 Telemedicine Encounters During the COVID-19 Pandemic

Abstract: Abstract:Objective:To examine if telemedicine remains safe and of high quality despite rapid expansion of services by comparing telemedicine encounters prior to and during COVID 19 pandemic.Methods:Pre-post study investigating 2999 telemedicine encounters: 2/1/2020 - 5/15/2020. 2919 completed visits before and after strict social distancing implementation were analyzed for patient and provider characteristics, encounter characteristics (history, physical exam, etc) and quality and safety metrics (phone calls &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 12 publications
(8 reference statements)
0
31
1
Order By: Relevance
“…Pediatric neurologists are not exempt from this, especially those managing pediatric headache. Unfortunately, to date, only a few studies have examined the use of telemedicine in pediatric headache; however, all have shown excellent promise [ 4 ••, 8 •, 26 , 33 •, 34 •].…”
Section: Telemedicine In Pediatric Headachementioning
confidence: 99%
See 4 more Smart Citations
“…Pediatric neurologists are not exempt from this, especially those managing pediatric headache. Unfortunately, to date, only a few studies have examined the use of telemedicine in pediatric headache; however, all have shown excellent promise [ 4 ••, 8 •, 26 , 33 •, 34 •].…”
Section: Telemedicine In Pediatric Headachementioning
confidence: 99%
“…Within 8–30 days of the visit, 0.8 percent of patients were admitted and no deaths were seen throughout the entire study. While this study analyzed all pediatric neurology patients seen via telemedicine, at least 594 of them were diagnosed with headache or migraines [ 34 •]. This study also found that there was no difference in the rate of subsequently performed in-person examinations nor hospitalizations when comparing new and established telemedicine patients [ 34 •].…”
Section: Telemedicine In Pediatric Headachementioning
confidence: 99%
See 3 more Smart Citations